2007
DOI: 10.1210/en.2007-0930
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer Binding Protein β, But Not Steroidogenic Factor-1, Modulates the Phthalate-Induced Dysregulation of Rat Fetal Testicular Steroidogenesis

Abstract: Prolonged in utero exposure of fetal male rats to dibutyl phthalate (DBP) can result in a feminized phenotype characterized by malformed epididymides, hypospadias, cryptorchidism, and retained thoracic nipples, among others. These symptoms likely result, in part, from decreased expression of steroidogenic enzymes and, therefore, reduced testosterone biosynthesis. However, the molecular mechanisms involved in these changes in gene expression profiles are unknown. To understand these mechanisms in rats, in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…DBP inhibits NR5A1 binding in the promoters and introns of NR5A1-transactivated genes (such as Cyp11a1 , Cyp17a1 , and Star ) that are down-regulated by DBP (Plummer et al, 2013). The binding of NR5A1 to the NR5A1-transactivated gene promoter of Fshr is not affected phthalates (Kuhl et al, 2007; Plummer et al, 2007; Plummer et al, 2013), conforms to the unaltered Fshr expression after the treatment of phthalates (DEHP, DBP, and DINP) (Kuhl et al, 2007; Plummer et al, 2007; Lin et al, 2008a; Plummer et al, 2013; Li et al, 2014), therefore suggesting that the effects of phthalates on NR5A1 binding are indirect. The suppressive actions of phthalates on the binding of NR5A1 to the NR5A1-mediated steroidogenic genes correlate with profiles in the binding of PPARα, a subtype nuclear receptor of PPAR (Plummer et al, 2013).…”
Section: Phthalate Exposuresupporting
confidence: 60%
See 1 more Smart Citation
“…DBP inhibits NR5A1 binding in the promoters and introns of NR5A1-transactivated genes (such as Cyp11a1 , Cyp17a1 , and Star ) that are down-regulated by DBP (Plummer et al, 2013). The binding of NR5A1 to the NR5A1-transactivated gene promoter of Fshr is not affected phthalates (Kuhl et al, 2007; Plummer et al, 2007; Plummer et al, 2013), conforms to the unaltered Fshr expression after the treatment of phthalates (DEHP, DBP, and DINP) (Kuhl et al, 2007; Plummer et al, 2007; Lin et al, 2008a; Plummer et al, 2013; Li et al, 2014), therefore suggesting that the effects of phthalates on NR5A1 binding are indirect. The suppressive actions of phthalates on the binding of NR5A1 to the NR5A1-mediated steroidogenic genes correlate with profiles in the binding of PPARα, a subtype nuclear receptor of PPAR (Plummer et al, 2013).…”
Section: Phthalate Exposuresupporting
confidence: 60%
“…Gene expression studies suggest that phthalates (e.g. DBP) affect steroidogenic gene expression via indirect suppression of NR5A1 action in fetal rat testes (Kuhl et al, 2007; Plummer et al, 2007). DBP inhibits NR5A1 binding in the promoters and introns of NR5A1-transactivated genes (such as Cyp11a1 , Cyp17a1 , and Star ) that are down-regulated by DBP (Plummer et al, 2013).…”
Section: Phthalate Exposurementioning
confidence: 99%
“…Sertoli cells exposed to chromium(III) chloride have been reported to increase levels of Cebpa mRNA, which may influence germ cell development by altering downstream target gene expression [34]. Fetal exposure to dibutyl phthalate (DBP) inhibits steroidogenic genes by decreasing the DNA-binding activity of CEBPB [35]. These studies demonstrated the common participation of the CEBP family after toxicant-induced testicular injury.…”
Section: Discussionmentioning
confidence: 94%
“…Activated PPAR can repress gene expression in a DNA-binding-independent manner through the recruitment of corepressors or by interfering with other DNA-associated transcription factors (65,66). Recently phthalates were also reported to act by decreasing recruitment of the transcription factor CCAAT/enhancerbinding protein-␤ to DNA but having no effect on SF1 (69). Although the exact mechanism remains to be identified, we found that the phthalate MEHP antagonizes AR action through a region of the Insl3 promoter known to bind transcriptional activators, which suggests that disruption of transcription factor interactions might be involved.…”
Section: Androgen-mehp Antagonism In Insl3 Transcriptionmentioning
confidence: 99%